Pengaruh Insentif Pajak Terhadap Efektivitas Kebijakan Pemulihan Ekonomi Nasional Pada Pelaku UMKM yang Terdampak Covid-19 Di KPP Pratama Parepare - Ihqram, Magfiratuh; Burhan, Imron; Sari, Sri (Income Journal: Accounting, Management and Economic Research, 2023)
The purpose of this study was to determine the Effect of Tax Incentives on the Effectiveness of the National Economic Recovery Policy (PEN) on UMKM Actors Affected by Covid-19 at KPP Pratama Parepare. This study uses quantitative research that processes primary data and secondary data with data collection techniques using questionnaires. The number of samples in this study were 100 UMKM Taxpayers. The data analysis technique used is multiple linear regression analysis using SPSS 20. The results show that tax incentives affect the effectiveness of the national economic recovery (PEN) policy on UMKM actors affected by COVID-19. The national economic recovery policy in providing this tax incentive to UMKM actors affected by COVID-19 can increase UMKM income.